ANALISIS TEGANGAN-REGANGAN, TEKANAN AIR PORI DAN STABILITAS MODEL DAM TIMBUNAN TANAH - Sompie, Oktovian B. A.; Pontororing, Christian (Sam Ratulangi University, 2014)
The need of dam is considered necessary for an area, the residential area located in the Watershed (DAS) experience frequent flooding when the river water is at high water level. That is why we need to learn the behavior of the soil embankment dams associated with the stress-strain, pore water pressure and stability to obtain a soil embankment dam design is safe from collapse or failure. Various ways can be done to analyze it, one of which program is to make a model dam with a calculation using the program Plaxis. In modeling this dam soil was taken from the site Doloduo II, Kotamobagu, namely silty clay then modeled in an experimental box. Dams were given treatment in the form of the addition of water to a certain height. Dam stability is observed with pore water pressure and other things that happened in the modeling, then compared with analysis using Plaxis 3D Foundation program is made in three calculation process. Keyword: Modeling of dam, Stress-Strain, Pore Water Pressure, Program Plaxis.